Slaughter and carcass characteristics, and meat quality in Holstein Friesian, Eastern Anatolian Red and crossbreed (F1) bulls fed at high altitude - Sadrettin Yüksel; Alpay Karaçuhalılar (Journal of Central European Agriculture)
The study aimed to determine the slaughter traits, carcass characteristics and meat quality of Eastern Anatolian Red (EAR), Holstein Friesian (HF) and their crossbreed (F1) bulls to provide a different systematic structure to red meat production for sustainable meat production. The present research applied the rearing and feeding method commonly used in the region. The experiment was conducted at a high altitude, and comprised in total of 10 Eastern Anatolian Red (HFEAR) bulls, 6 Holstein Friesian (HF) bulls and 6 Holstein Friesian × Eastern Anatolian Red (HFEAR) bulls (Eastern Anatolian Red dams sired by Holstein Friesian) crossbred bulls that had 15-month ages. The objective for slaughter age in the experiment was 20 months (150 days) which is the average slaughter age for beef bulls. The slaughter and carcass characteristics and carcass measurements were determined by the measurement and weighing. Marbling score, fat thickness over longissimus dorsi (FatT), carcass conformation (CarC), fat cover score (FCS), colour (L*, a*, b*) and organoleptic traits (tenderness, juiciness, flavour) were determined in the longissimus dorsi (LD) muscle from carcass representative of the experimental bulls. The results indicated that initial weight (InW), final weight (FW), hot carcass weight (HoW), dressing (Drs%), head weight (HeW), four feet weight (FFW), hide weight (HiW), kidney weight (KidW), liver weight (LivW), pelvic fat weight (PFW), pH, carcass length (CarL), round length (RoL), round width (RoW) were associated with breed (P < 0.01). Significant differences were determined among fat thickness over LD (FaT, P < 0.05), longissimus dorsi area (LDA, P < 0.05), carcass conformation (CarC, P < 0.05), fat cover score (FCS, P < 0.05), L* (P < 0.01), a* (P < 0.01). At the same time, there were no significant marbling scores, pH, or b* differences among breeds (P > 0.05). HF bulls had a greater total weight gain (TWG) (P < 0.01), average monthly weight gain (AMWG) (P < 0.05), average daily weight gain (ADWG) (P < 0.01) and sensory analysis (except flavour) (P < 0.05) in comparison to the EAR bulls. Contrary to the prejudice that was no suitable material for fattening at high altitudes; fattening performance, carcass characteristics and meat quality values of cattle obtained by crossbreeding Holstein Friesian and local breed bulls were found to be at standard level, in this study.